Hierarchical Interface-Based Decentralized Supervisory Control - Liu, Huailiang (My University, 2015)
In decentralized control, agents have only a partial view and partial control of the system and must cooperate to achieve the control objective. In order to synthesize a decentralized control solution, a specification must satisfy the co-observability property. Existing co-observability verification methods require the possibly intractable construction of the complete system. To address this issue, we introduce an incremental verification of co-observability approach. Selected subgroups of the system are evaluated individually, until verification is complete. The new method is potentially much more efficient than the monolithic approaches, in particular for systems composed of many subsystems, allowing for some intractable problems to be manageable. Properties of this new strategy are presented, along with a corresponding algorithm and an example. To further increase the scalability of decentralized control, we wish to adapt the existing Hierarchical Interface-Based Supervisory Control (HISC) to support it. We introduce the Hierarchical Interface-Based Decentralized Supervisory Control (HIDSC) framework that extends HISC to decentralized control. To adapt co-observability for HIDSC, we propose a per-component definition of co-observability along with a verification strategy that requires only a single component at a time in order to verify co-observability. Finally, we provide and prove the necessary and sufficient conditions for supervisory control existence in the HIDSC framework and illustrate our approach with an example. As the entire system model never needs to be constructed, HIDSC potentially provides significant savings.
Keywords: Discrete-event systems (DES); Supervisory control of DES; Decentralized control; State-space explosion problem